The Impact of Teacher Characteristics on Educational Differentiation Practices in Lower Secondary Mathematics Instruction - Ekstam, Ulrika; Linnanmäki, Karin; Aunio, Pirjo (LUMAT: International Journal on Math, Science and Technology Education, 2017)
This study aimed to investigate how teachers’ certification status, experience in instruction, and teachers’ efficacy beliefs for teaching lower secondary students in mathematics are related to differentiated instruction practices. A total of 42 mathematics teachers and 27 special education teachers answered an electronic questionnaire regarding mathematics teaching efficacy beliefs and their frequency of use of differentiation practices. The results indicated that teachers’ efficacy beliefs were related to differentiation in content, flexible examination models, homework support, and co-teaching. Neither certification status nor teacher experience in instruction was related to the frequency of use of differentiation practices. As teacher efficacy beliefs seem to have an effect on the use of differentiation practices, and especially on co-teaching, it should be important for teacher education to focus on developing pre-service teachers’ efficacy beliefs as well as implementing a strong collaboration between different teacher groups.